Integration of longitudinal psychoeducation programmes during the phases of diagnosis, management and survivorship of breast cancer patients: A narrative review. (March 2020) - Michaelides, Athena; Constantinou, Constantina
Highlights: Psychoeducation programmes should: Use a patient-centred approach to evaluate the patients' needs, concerns and expectations and provide emotional support to reduce anxiety. Be longitudinal to address the patients' needs at different stages (diagnosis, management, survivorship). Use the most effective combination of communication methods that address the patients' needs at different stages. Address the needs of families, friends and caregivers of breast cancer patients. Abstract: Breast cancer is the second most common cancer diagnosed worldwide and the leading cause of cancer death in women. In the past years, efforts have been made to develop psychoeducation programmes targeting the prevention of breast cancer via educating the general public. These programmes placed emphasis on risk reducing behaviours and on promoting Breast Self-Examination and screening via mammography, to aid in the early identification of pathological findings. In parallel, efforts have been made to develop psychoeducation interventions to support breast cancer patients during the phases of diagnosis, management and survivorship. The current review sheds light on the need to develop psychoeducation programmes in the future that will (a) be patient centred, (b) focus on emotional support to reduce the patients' anxiety, (c) be longitudinal to address the patients' specific needs at the different stages of diagnosis, management and survivorship, (d) apply the most effective combination of communication methods and (e) address the needs of both cancer patients but also those of their families, friends and caregivers. The ultimate goal is to develop psychoeducation programmes that will benefit both the mental and physical health of the patients and ultimately improve their prognosis.